An autoregressive jump process for common stock returns - Oldfield, George S.; Rogalski, Richard J.; Jarrow, Robert A. (Journal of Financial Economics, 1977)
This paper develops a new distribution theory for common stock returns. The model is composed of a calendar time diffusion process and a jump process where the magnitudes of the jumps may be autocorrelated. Empirical tests are performed on a month of transactions returns for twenty New York Stock Exchange securities. The data analysis supports the validity of the proposed theory.